2015
DOI: 10.1103/physrevb.91.075109
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiotheory of spin entanglement in atoms and molecules

Abstract: We investigate spin entanglement in many-electron systems within the framework of density functional theory. We show that the entanglement length, which is extracted from the spatial dependence of the local concurrence, is a sensitive indicator of atomic shells, and reveals the character, covalent or metallic, of chemical bonds. These findings shed light on the remarkable success of modern density functionals, which tacitly employ the entanglement length as a variable. This opens the way to further research on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…They are in fact extremely relevant for all those studies and applications where a semilocal model of the KED is important. Here we suggest, for example, the evaluation of local indicators such as the electron localization function (ELF) [89,90] or the entanglement length [91]. These are density indicators but they are actually obtained as orbital-dependent expressions due to the presence of τ KS .…”
Section: Discussionmentioning
confidence: 99%
“…They are in fact extremely relevant for all those studies and applications where a semilocal model of the KED is important. Here we suggest, for example, the evaluation of local indicators such as the electron localization function (ELF) [89,90] or the entanglement length [91]. These are density indicators but they are actually obtained as orbital-dependent expressions due to the presence of τ KS .…”
Section: Discussionmentioning
confidence: 99%
“…Function t GBP ðrÞ is found to be related to the first spectral moment of the optical conductivity tensor, therefore t GBP ðrÞ reflects some electron localization properties. That explains why the electronic kinetic energy density is a part of several localization and metallicity descriptors (as ELF, LOL, and some others [117][118][119] ). Also, it is shown that the previously introduced PS-FID, describing local information about electron momentum in the position space, is somewhat similar with PVD function.…”
Section: Su M M a R Ymentioning
confidence: 99%
“…Analyses of electron localization are also important because they offer insights for improving density functional constructions 10 . The ELF has been connected to the ability of density functional approximations to access local information on the spin-entanglement 11 , to properties of the electronic stress tensor 12 , and to timedependent density functionals 13 . The interpretation of the ELF, however, is not free from difficulties 14,15 .…”
Section: Introductionmentioning
confidence: 99%